Computed Tomography (CT) attenuation value in relation with body dimension, gender and age in Malay population: A Literature Review / Siti Aisyah Munirah Bohang ... et al.] - Bohang, Siti Aisyah Munirah; Zainuddin, Zainul Ibrahim; Suhoimi, Norhanna (Universiti Teknologi MARA Cawangan Selangor, 2020)
Interaction of CT's x-ray beams with patient resulted in attenuation process and there are various factors affecting CT attenuation values. The aim of this review is to examine the existed literatures regarding the concept of attenuation in CT and its relationship with body dimension, gender and age in Malay population. Guided by primary question, literature searches were conducted using the established online database; SCOPUS and PubMed. The time frame for literatures was from 2000 to 2019 and only literatures in English language were selected. The size of body dimension has affected the CT attenuation value but it also depending on the type of tissue presence within the region of interest (ROI) such as muscle and fat tissues. Due to larger body framework and higher amount of skeletal muscle mass theoretically males would have higher CT attenuation value than female. CT attenuation value reduces with aging process. Asians including Malay population have smaller body dimension than Caucasians and the mean attenuation value of abdominal region in Asians could differ from 20 HU. Thus, there is a need for future research to investigate the interrelatedness of attenuation in CT (HU) and body dimension within Malay population and close this gap of knowledge.